2001
DOI: 10.1074/jbc.m101714200
|View full text |Cite
|
Sign up to set email alerts
|

The p42/p44 Mitogen-activated Protein Kinase Activation Triggers p27Kip1 Degradation Independently of CDK2/Cyclin E in NIH 3T3 Cells

Abstract: The p42/p44 mitogen-activated protein (MAP) kinase is stimulated by various mitogenic stimuli, and its sustained activation is necessary for cell cycle G 1 progression and G 1 /S transition. G 1 progression and G 1 /S transition also depend on sequential cyclin-dependent kinase ( Kip1 expression in fibroblasts essentially through a degradation mechanism, independently of p27 Kip1 phosphorylation by CDK2. This strengthens the role of this CDK inhibitor as a key effector of G 1 growth arrest, whose expression ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 58 publications
3
47
1
Order By: Relevance
“…In fibroblasts, activa-tion of MAP kinases leads to an increase in p27 Kip1 degradation that is independent of phosphorylation by CDK2/cyclin E [39,40,41]. In contrast, a more delayed and prolonged activation of MAP kinases, for example induced in PC12 cells and fibroblasts by nerve growth factor, leads to cell cycle arrest [42].…”
Section: Discussionmentioning
confidence: 99%
“…In fibroblasts, activa-tion of MAP kinases leads to an increase in p27 Kip1 degradation that is independent of phosphorylation by CDK2/cyclin E [39,40,41]. In contrast, a more delayed and prolonged activation of MAP kinases, for example induced in PC12 cells and fibroblasts by nerve growth factor, leads to cell cycle arrest [42].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of ERK by PD98059 causes an accumulation of p27 as well as the S phase entry in fibroblasts and epithelial cells (33), suggesting that the ERK cascade is required for both mitogen-induced p27 down-regulation and proliferation. Furthermore, genetic activation of ERK decreased the expression of p27 in NIH 3T3 cells (34).…”
Section: Figmentioning
confidence: 95%
“…The levels of p27 are high in quiescent cells and decline in response to mitogenic factor stimulation. Several studies have suggested that the Ras-ERK1/2 signaling pathway is involved in the mitogen-induced downregulation of p27 (Kawada et al, 1997;Kerkhoff and Rapp, 1997;Woods et al, 1997;Greulich and Erikson, 1998;Rivard et al, 1999;Treinies et al, 1999;Lenferink et al, 2000;Yang et al, 2000;Delmas et al, 2001;Mirza et al, 2004;Gysin et al, 2005;Sakakibara et al, 2005). In contrast, other studies failed to document any significant change in p27 levels following inhibition of ERK1/2 signaling by synthetic MEK1/2 inhibitors or dominant-negative ERK2, or after conditional activation of the pathway by activated Raf-1 or MEK1 (Sewing et al, 1997;Takuwa and Takuwa, 1997;Weber et al, 1997a;Cheng et al, 1998;Ladha et al, 1998;Chen et al, 1999;Tetsu and McCormick, 2003).…”
Section: Erk1/2 Map Kinases In Cell Cycle Control S Meloche and J Poumentioning
confidence: 99%
“…The degradation of p27 at the G1/S transition depends on the accumulation of cyclin E and concomitant activation of Cdk2, events that are conditional on earlier activation of cyclin D-Cdk4/6 complexes by the ERK1/2 pathway. However, there is evidence that ERK1/2 signaling can trigger downregulation of p27 expression by a Cdk2-and Skp2-independent mechanism (Delmas et al, 2001;Mirza et al, 2004). Activation of the ERK1/2 pathway may also contribute indirectly to p27 regulation through the synthesis of autocrine growth factors.…”
Section: Erk1/2 Map Kinases In Cell Cycle Control S Meloche and J Poumentioning
confidence: 99%